Cutting Load on Public Health System by Correcting Population Diet: Economic Aspect - S. N. Masterova (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
Investment in programs aiming at healthy life and diet popularization has social and economic importance and significant in view of medicine. Balanced diet can cut the risk of many chronic illnesses, such obesity, cardiovascular diseases and diabetes. At the same time it can result in lower costs of their treatment. Apart from that, healthy food can help raise productivity and reduce the number of sick-leave days of people, which can be considered as an economic benefit for society. Methodological base of the research is formed by studying the correlation between balanced diet of the population and load on public health system of the country. The analysis provided in the article shows that improper diet increases costs of public health system, as more reserves are necessary to treat illnesses. It affects budgets of the public health system in the country and can deteriorate accessibility of medical help for a lot of people.